Analyzing the Effects of Interest Rates, Inflation, and Exchange Rates on Stock Market Performance: A Comparative Study Of Indonesia and Japan - Majok, Alith Jacob; Kaluge, David; Satria, Dias (Journal of Indonesian Applied Economics, 2024)
Purpose This study examines the influence of macroeconomic variables on stock market performance in Indonesia and Japan from 2013 to 2023. Drawing upon the Efficient Market Hypothesis (EMH), we investigate how key factors such as interest rates, inflation, exchange rates, and economic events impact stock returns. Design/methodology/approach We examine the connections between these characteristics and stock market performance in two different markets using regression analysis and EMH as the theoretical framework. In order to find patterns and trends, we analyze data spanning a decade. Findings Interest rates strongly affect Indonesian stocks due to their influence on investor sentiment. In Japan, trade agreements have a significant positive impact on stock returns. However, stock returns in both countries are weakly connected to inflation, currency rates, and other economic and political factors. The global economy remains a key external factor for both markets. Research limitations/implications This study has some restrictions, such as data limitations and EMH framework-related presumptions. In the future, research may focus on longer-term effects, behavioral aspects, and sector-specific analysis to further our comprehension of these intricate interactions. Originality/value This research advances our understanding of market behavior under various economic conditions by analyzing the interaction of macroeconomic variables and stock market dynamics in two distinct economies.